Реализация операции умножения с использованием преобразования Уолша - Терещенко, А.Н.; Мельникова, С.С.; Гнатив, Л.А.; Задирака, В.К.; Кошкина, Н.В (Проблемы управления и информатики, 2010)
Показано реалізацію операції множення на основі циклічної згортки і обчислення циклічної згортки з використанням перетворення Уолша. Наведено кількісну оцінку операцій однослівного множення для методу Уолша. Запропонований метод проілюстровано при реалізації згорток довжиною 4 і 8. Представлено дані, необхідні для обчислень згорток розрядністю 8 і 16. Наведено формули обчислень циклічної згортки довжиною N = 2ⁿ з використанням перетворення Уолша. Описано резерви оптимізації обчислень. It is shown how to calculate the multiplication based on circular convolution and how to calculate the circular convolution using Walsh transform. The number of single precision multiplications is given. The method is illustrated with calculation of 4 and 8-length convolutions. The data for calculation of 8 and 16-length convolution are given. The N = 2ⁿ-length convolution calculation formulas with using Walsh transform are given. Calculation optimization reserves are described.